Improving the manufacturing process of wooden pallets: A case study (2017)
Introduction: This article shows the results of the applied research project “Improved design of the manufacturing process of wooden pallets through tools for increasing productivity. Case: Wood industry”, conducted at the Fundación Universitaria Tecnológico Comfenalco Cartagena during 2014. The objective of the research was to create and apply improvement actions to the productive process of the company studied based on industrial engineering tools that would allow a better use of available resources. Methodology: Methods and methodologies were applied to increase productivity, such as the methods-time measurement and the 5S methodology, a guide to implement a cleaner production (cp) program and to calculate the yield of raw materials. Results: The production process was standardized and improved based on the methods-time measurement and 5S. A reasonable production standard was established for the company and its workers. A methodology to calculate wood yields was assessed. A proposal was prepared to implement a cp program, whose guidelines improved the operating practices. Conclusion: Not measuring a process is as serious as measuring it wrongly, since it can lead to the implementation of non-compliant or very lax standards, as well as to a work environment with low levels of productivity due to employee dissatisfaction with inadequate demands, or to the relaxation of employees. Therefore, work study today is highly valid and applicable.